Students’ Responses in Online Learning During the Covid-19 Pandemic Towards Mathematics Learning Outcomes of Students - Azis Azis; Rasmuin Rasmuin; Rahmatia Rahmatia (Square : Journal of Mathematics and Mathematics Education, 2022)
The purpose of this study was to determine the effect of student responses in online learning during the Covid-19 pandemic on the mathematics learning outcomes of grade IX students at the junior high school level and the equivalent in Baubau City. This research is an ex-post facto research, which was conducted in junior high school and equivalent in Baubau City. The population is all students of class IX SMP and equivalent in Baubau City (that is, SMP and MTs both public and private) as many by as 3170 students. The research sample was taken as many as 314 students. The instruments used are questionnaires and tests of students' mathematics learning outcomes. The results of the analysis on the regression test with a significant value of 0.024 0.025 and a t-value of 2.266 state that there is an effect of student responses in online learning on the mathematics learning outcomes of grade IX junior high school students and the equivalent in Baubau City.Keywords: student response, online learning, the covid-19 pandemic, mathematics learning outcomes